ENHANCING CRITICAL THINKING SKILL THROUGH STEM E-LKPD ASSISTED BY LIVEWORKSHEETS ON ADVANCED CLARIFICATION INDICATORS - Isra, Silvya; Syukri, Muhammad; Saminan, Saminan; Maghfirah, Siti; Hamid, Abdul (EduFisika: Jurnal Pendidikan Fisika, 2025)
Students' ability to think critically, particularly in terms of providing advanced clarification, is still relatively low. Therefore, innovative learning media is needed to encourage the development of these skills. This study aims to analyze the effectiveness of STEM-based Student Worksheets (LKPD) assisted by liveworksheets in improving students' critical thinking skills in physics learning. These LKPD are designed by integrating the Engineering Design Process (EDP) stages of the STEM approach. The study was conducted using a quantitative approach with a one-group pretest-posttest pre-experimental design. The research subjects consisted of 33 students from class X 1 of SMA Negeri 5 Banda Aceh, selected through purposive sampling. The research instrument was an essay question to measure students' critical thinking skills, analyzed using the Shapiro-Wilk normality test, N-Gain test, and Wilcoxon Signed-Rank test. The analysis results showed a significant increase after the intervention, with an average N-Gain of 0.94, which falls into the high category, and a significance value of 0.000 (<0.05). These findings indicate that the use of STEM-based E-LKPD integrated with liveworksheet is an effective and contextual learning strategy in developing students' critical thinking skills.